CLASS ACTION PENCEMARAN LAUT TERHADAP BADAN USAHA PERTAMBANGAN : Studi Kasus Putusan Nomor 26 / Pdt. G / 2009 / PN. TPI )”. - Cucuk Endratno (Populis : Jurnal Sosial dan Humaniora, 2016)
The  law in environment destruction  done either by individuals or corporations has been enacted in terms of both prevention and repression. In the prevention domain, several instruments have been provided and implemented in ways that take into consideration the destruction impacts on the hazard of environment. Such instruments include administrative penalties, and those tackling  the problems voiced by class actions. This study focuses on a case of Putusan Nomor 26 / Pdt. G / 2009 / PN. TPI ) that tackles the class action by coastal fishermen of Sondong along the Coast of Senggarang, Kecamatan Tanjung Pinang Kota, the Province of Riau. The method used is qualitative research method. The study finds that the case is won by the fishermen community in the locality and the fine is imposed to the corporation. Keywords: law enforcement, the case of mining corporation vs. fishermen at  Kecamatan Tanjung Pinang Kota, class action.